TEKNIK BERACARA DALAM PEMBUKTIAN PIDANA KEPADA WARGA LEMBAGA PEMASYARAKATAN RUMAH TAHANAN NEGARA SALEMBA KELAS 1 - Firmansyah, Hery; Hugo Feris Tri Susanto; Ahmad Muzacky; Matthew Mikha Sebastian Matondang; Deryl Leeland; Indri Elena Suni (Jurnal Serina Abdimas, 2025)
One of the most crucial processes in handling criminal cases is the stage of proof in court. A person cannot be convicted of a criminal act if there is no valid evidence to support the accusation. According to Indonesian law, specifically the Criminal Procedure Code (KUHAP), a criminal case cannot proceed to conviction unless there are at least two valid pieces of evidence. If the evidence presented does not meet this requirement or is obtained unlawfully, it cannot be used as a basis for punishment. Recognizing the importance of legal awareness in correctional facilities, the UNTAR Faculty of Law (FH) Legal Aid and Consultation Center (PKBH) Team carried out a legal counseling session at the Salemba Class I Detention Center in Central Jakarta. This activity was a collaboration between lecturers, legal practitioners (lawyers), and students, and is part of the implementation of the Tri Dharma of Higher Education—particularly community service and legal education. The material presented focused on the implementation of criminal trials as regulated under Law Number 8 of 1981 concerning the Criminal Procedure Code. Special attention was given to Article 184, which outlines the types of admissible evidence: Witness Statements, Expert Testimonies, Documentary Evidence, and Indications. The goal of this counseling activity was to provide inmates with a deeper understanding of the evidentiary process in criminal law. With this knowledge, inmates are expected to be more aware of their rights and better understand procedures during trial. The session received a positive response and participation from the inmates. ABSTRAK Salah satu proses penting dalam penanganan kasus pidana adalah tahap pembuktian di persidangan. Hal ini sangat krusial karena seseorang tidak dapat dijatuhi hukuman atas suatu perbuatan pidana tanpa adanya alat bukti yang sah dan cukup. Menurut Kitab Undang-Undang Hukum Acara Pidana (KUHAP), minimal harus terdapat dua alat bukti yang sah agar seseorang dapat dinyatakan bersalah. Apabila jumlah alat bukti tidak mencukupi atau alat bukti diperoleh dengan cara yang tidak sah, maka hal tersebut tidak dapat digunakan dalam proses pembuktian di persidangan. Berdasarkan hal tersebut, Tim Pusat Konsultasi dan Bantuan Hukum Fakultas Hukum Universitas Tarumanagara (PKBH FH UNTAR) melaksanakan kegiatan penyuluhan hukum di Rumah Tahanan Salemba Kelas I Jakarta Pusat. Kegiatan ini merupakan bentuk kerja sama antara dosen, praktisi hukum (pengacara), dan mahasiswa dalam rangka menjalankan Tri Dharma Perguruan Tinggi, khususnya pengabdian kepada masyarakat. Materi yang disampaikan dalam penyuluhan ini adalah mengenai pelaksanaan persidangan dalam perkara pidana yang diatur dalam Undang-Undang Nomor 8 Tahun 1981 tentang Hukum Acara Pidana. Fokus utama penyuluhan ini adalah pembahasan mengenai alat bukti sebagaimana diatur dalam Pasal 184 KUHAP, yaitu Keterangan Saksi, Keterangan Ahli, Surat, dan Petunjuk. Tujuan utama dari kegiatan ini adalah untuk memberikan pemahaman yang lebih baik kepada warga binaan mengenai proses pembuktian dalam hukum pidana Indonesia agar mereka memahami hak-haknya dalam proses peradilan.